2016
DOI: 10.1016/j.dam.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

On r-hued coloring of planar graphs with girth at least 6

Abstract: a b s t r a c tFor integers k, r > 0, a (k, r)-coloring of a graph G is a proper k-coloring c such that for any vertex v with degree d(v), v is adjacent to at least min{d(v), r} different colors. Such coloring is also called as an r-hued coloring. The r-hued chromatic number of G, χ r (G), is the least integer k such that a (k, r)-coloring of G exists. In this paper, we proved that if G is a planar graph with girth at least 6, then χ r (G) ≤ r + 5. This extends a former result in Bu and Zhu (2012). It also imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…, where r ≥ 1. The notion of r-dynamic coloring was introduced by Montgomery [30], newly studied [19,18], and also investigated under the notion of r-hued coloring [11,27,31,32,33,41]. As starting cases of r-dynamic coloring, the 2-dynamic coloring (known as dynamic coloring in literature) [4,1,2,3,8,10,23,26,29,28] and the 3-dynamic coloring [5,21,25] have been considered.…”
Section: List 3-dynamic Coloringmentioning
confidence: 99%
“…, where r ≥ 1. The notion of r-dynamic coloring was introduced by Montgomery [30], newly studied [19,18], and also investigated under the notion of r-hued coloring [11,27,31,32,33,41]. As starting cases of r-dynamic coloring, the 2-dynamic coloring (known as dynamic coloring in literature) [4,1,2,3,8,10,23,26,29,28] and the 3-dynamic coloring [5,21,25] have been considered.…”
Section: List 3-dynamic Coloringmentioning
confidence: 99%
“…Lai et al [14] showed the conjecture 1.1 is true for planar graphs with girth at least 6. Several results about r-dynamic coloring were published in [1,2,5,6,7,11].…”
Section: Introductionmentioning
confidence: 99%
“…And Cheng et al [3] studied the maximum average condition to have χ d 3 (G) ≤ 4, 5, or 6. On the other hand, Song et al [14] showed that if G is planar with girth at least 6, then χ d r (G) ≤ r + 5 for any r ≥ 3. In this paper, we study list 3-dynamic coloring in terms of maximum average degree.…”
mentioning
confidence: 99%